Optimal Sizing of Hybrid Systems and Economical Comparison - Navaeefard, Arash; Babaee, Omid; Radmanesh, Hamid (International Journal of Sustainable Energy and Environmental Research, 2017)
Aim of study finding the best configuration among a set of system components. Power fluctuations and load disturbances in hybrid systems cause power inequality and system stability problems. Using hybrid energy storage systems is an effective solution in order to overcome unbalancing between power generating and load demands. In this paper, a methodology to perform the optimal sizing for Distributed Energy Resources (DERs) in three hybrid systems is developed, and reliability index is considered as a constraint. The optimum system configuration can meet the customer’s required Equivalent Loss Factor (ELF=0) with the minimum cost, and comparison cost between them. In these configurations, power generators are photovoltaic (PV)/wind turbine and three combination of battery bank and hydrogen tank is used as an energy storage system. Particle Swarm Optimization (PSO) algorithm has been used to optimize the cost function, and has been simulated in MATLAB for justification purpose.